A new model considering the morphological changes of cake and gel for the in-situ membrane cleaning process. Issue 6 (December 2021) - Wang, Zhan; Guo, Yangyang; Qiao, Zhaoyu
Abstract: Understanding the hydraulic cleaning mechanism of the membrane fouled with activated sludge (AS) and establishment of the flux predictive model can effectively improve the cleaning efficiency of the membrane in MBR. In this study, an instantaneous flux prediction model was established by considering the cascade mechanisms (irreversible swelling, reversible dissolution and re-deposition) for the gel and dynamic equilibrium mechanisms (direct reversible dissolution and re-deposition) for the cake in the hydraulic cleaning process. In addition, the XDLVO theory was used to calculate the variation of interaction energy between AS and membrane surface in the swelling process of AS. The result showed that the proposed model was fully adequate for the 200 kDa PAN membrane fouled with AS suspension ( R 2 =0.9987) or yeast suspension ( R 2 =0.9958) in the hydraulic cleaning process. The swelling of AS can significantly reduce the attractive interaction energy and improve the membrane cleaning efficiency. Moreover, the predictive model showed better accuracy (σ = 0.39%) than other models (Kong's model (σ = 0.71%) and Cabero's model (σ = 0.88%)). In addition, the proposed model also exhibited excellent performance for the multiple fouling and cleaning processes ( R 2 >0.9860) and for other membranes (100 kDa PES membrane ( R 2 =0.9995), 200 kDa PVDF membrane ( R 2 =0.9976) and 0.1 µm PAN membrane ( R 2 =0.9999)) fouled with AS suspension. Graphical Abstract: ga1 Highlights: The hydraulic cleaning mechanism of gel and cake was fully studied. The hydraulic cleaning model of activated sludge was firstly determined. This model can be used to predict the membrane flux in the cycle cleaning process. The predictive fluxes have a good agreement with the experimental fluxes.